Pelatihan Pembuatan Media Interaktif Blog Pada Pembelajaran Fisika - Supartin Supartin; Trisnawaty J Buhungo (Universitas Negeri Gorontalo, 2026)
The rapid advancement of information and communication technology has increased the need for innovation in the teaching and learning process, particularly in physics education, which is often perceived by students as difficult and abstract. One promising approach is the use of digital learning media, such as interactive blogs, which enable learning materials to be presented in an engaging, flexible, and easily accessible manner. However, many physics teachers still lack the necessary competencies to design and develop blog-based learning media effectively. This community service program involved physics teachers who participated in training covering blog creation, content management, and the integration of physics learning materials in the form of text, images, videos, and interactive simulations. The program aimed to enhance teachers' competencies in designing and developing interactive blog-based learning media for physics instruction. The implementation consisted of four stages: socialization, training, mentoring, and participant evaluation. The program resulted in improved teachers' digital competencies, enabling them to develop interactive blog-based physics learning media and enhance the quality of classroom instruction. In addition, the program supports digital transformation in education while fostering students' learning motivation and improving learning outcomes.